Intrabiliary and abdominal rupture of hepatic hydatid cyst leading to biliary obstruction, cholangitis, pancreatitis, peritonitis and septicemia: a case report - Manouchehr Aghajanzadeh (Journal of Medical Case Reports, 2021)
Abstract Background Hydatid cysts are fluid-filled sacs containing immature forms of parastic tapeworms of the genus Echinococcus. The most prevalent and serious complication of hydatid disease is intrabiliary rupture, also known as cystobiliary fistulae. In this study, a sporadic case of biliary obstruction, cholangitis, and septicemia is described secondary to hydatid cyst rupture into the common bile duct and intraperitoneal cavity. Case presentation A 21-year-old Iranian man was admitted to the emergency ward with 5 days of serious sickness and a history of right upper quadrant abdominal pain, fatigue, fever, icterus, vomiting, and no appetite. In the physical examination, abdominal tenderness was detected in all four quadrants and in the scleral icterus. Abdominal ultrasound revealed intrahepatic and extrahepatic biliary duct dilation. Gallbladder wall thickening was normal but was very dilated, and large unilocular intact hepatic cysts were detected in segment IV and another one segment II which had detached laminated membranes and was a ruptured or complicated liver cyst. Conclusion Intrabiliary perforation of the liver hydatid cyst is an infrequent event but has severe consequences. Therefore, when patients complain of abdominal pain, fever, peritonitis, decreased appetite, and jaundice, a differential diagnosis of hydatid disease needs to be taken into consideration. Early diagnosis of complications and aggressive treatments, such as endoscopic retrograde cholangiopancreatography and surgery, are vital.